Plasma Estradiol and Testosterone Levels and Ischemic Stroke in Postmenopausal Women. Issue 4 (April 2020) - Hu, Jie; Lin, Jennifer H.; Jiménez, Monik C.; Manson, JoAnn E.; Hankinson, Susan E.; Rexrode, Kathryn M.
Abstract : Background and Purpose—: Although exogenous hormone therapy (HT) use has been associated with increased risk of ischemic stroke in postmenopausal women, it remains unknown whether sex hormone levels contribute to ischemic stroke risk. We aimed to estimate associations between plasma sex hormone levels and ischemic stroke risk, by HT status, in a nested case-control study of postmenopausal women from the NHS (Nurses' Health Study). Methods—: Women with confirmed incident ischemic stroke (n=419) were matched with controls (n=419) by age, HT use, and other factors. Plasma estradiol and testosterone levels were measured using liquid chromatography tandem mass spectrometry; SHBG (sex hormone-binding globulin) was assayed by electrochemiluminescence immunoassay. Associations of total and free estradiol and testosterone, the estradiol/testosterone ratio, and SHBG with ischemic stroke were estimated using conditional logistic regressions stratified by HT status with adjustment for matching and cardiovascular risk factors. Results—: Current HT users had different hormone profiles from never/past users. No clear linear trends were observed between estradiol (total or free) levels or the estradiol/testosterone ratio and ischemic stroke risk among either current users ( P trend >0.1) or never/past users ( P trend >0.6). For both current and never/past users, the associations between some of the sex hormones and ischemic stroke differed by body mass index categories ( P interaction ⩽0.04). For women with a body mass index <25 kg/m 2, a higher estradiol/testosterone ratio was associated with significantly elevated ischemic stroke risk among current users ( P trend =0.01), and higher levels of total and free estradiol were significantly associated with higher ischemic stroke risk among never/past users ( P trend ⩽0.04). Testosterone and SHBG were not associated with ischemic stroke in either current or never/past users. Conclusions—: Our findings do not support a role of sex hormone levels in mediating ischemic stroke risk among postmenopausal women. Replications in additional larger studies are required. Abstract : Supplemental Digital Content is available in the text.